Correction: Lei et al. Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus. Fishes 2024, 9, 452 - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2025)
In the original publication [...]